Dinámicas familiares del adulto mayor: Experiencias en la atención del centro residencial de Ceibopamba, en la actualidad. - Briceño Vega, Lucia Trinidad (2024)
Population aging is a global reality that poses both challenges and opportunities as life expectancy increases and birth rates decline, resulting in a higher proportion of older adults. Contrary to negative perceptions, many older adults are in good health and continue to play important roles in society. However, adaptation to residential facilities can be difficult, involving physical, emotional and social changes, and it is crucial to understand family dynamics to improve the quality of life of older adults in these settings. The objective of the research was to understand family dynamics and care at the Ceibopamba Residential Center from the perspectives of the older adult. The methodology used was based on a qualitative categorical approach, using semi-structured interviews and focus groups. The results indicate that women perceive greater emotional support compared to men, who feel greater disconnection and fewer visits. The family's economic situation and lack of time are important factors in the decision to admit the older adult to the residential center, and frequent visits tend to strengthen family ties. The main conclusions are that family dynamics have a strong influence on the emotional well-being of older adults in the residential center, and it was observed that older adults with better family relationships tend to be more emotionally and physically stable.